IMPLEMENTASI KEPEMIMPINAN LAPANGAN UNTUK MENCEGAH PENYALAHGUNAAN MEDIA SOSIAL PRAJURIT DI BATALYON INFANTERI MEKANIS RAIDER 412/BES - Kuntarti, Rita; Tjatur Supriyono; Purba, Apandi (JURNAL DWIJA KUSUMA, 2025)
He rapid development of information technology is marked by the use of social media as part of a lifestyle in all levels of society, including in the Indonesian Army. The widespread use of social media has many positive and negative impacts. In the Indonesian Army, the use of social media is not prohibited, but its use is limited and regulated by rules. In fact, there are still Indonesian Army soldiers who use social media not in accordance with the rules, including in the 412/BES Mechanized Infantry Battalion. The ease of access to social media anywhere and anytime is the cause of the difficulty in controlling the use of social media. The leadership aspect of a Commander is a strategic and urgent aspect to overcome this problem. A Commander needs to determine the right steps to be able to control the use of social media by members. The purpose of this paper is to analyze the role of the Commander (Danton) in implementing field leadership, to find out the obstacles to implementing field leadership, and to determine the right strategy to prevent misuse of social media by members. This study uses a qualitative method with the SWOT analysis technique. The data sources used by the author in this Final Project come from a number of books, journals, articles, field observations and interviews with related parties. From the results of the study, it was found that the most appropriate strategy to achieve the objectives of the paper is to implement the "SO" strategy or called the expansion strategy. This strategy is carried out by utilizing strengths to seize opportunities. The various activities and actions of Danton that have been designed in this writing are the embodiment of this strategy. The conclusion of this study can be said that the formulation of clear and detailed actions is very necessary so that Danton can implement field leadership in preventing the misuse of social media by members. Thus, field leadership is not just a theory but becomes a real action that Danton can implement in preventing the misuse of social media by members